2016
DOI: 10.2337/dc16-0155
|View full text |Cite
|
Sign up to set email alerts
|

HDL Cholesterol as a Residual Risk Factor for Vascular Events and All-Cause Mortality in Patients With Type 2 Diabetes

Abstract: OBJECTIVETo evaluate whether low HDL cholesterol (HDL-c) levels are a risk factor for cardiovascular disease and mortality in patients with type 2 diabetes and whether it remains a residual risk factor when attaining low LDL cholesterol (LDL-c) treatment goals or when LDL-c is treated with intensive lipid-lowering therapy. RESEARCH DESIGN AND METHODSWe performed a prospective cohort study of 1,829 patients with type 2 diabetes included in the Second Manifestations of ARTerial disease (SMART) cohort. Cox propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
(18 reference statements)
2
31
1
1
Order By: Relevance
“…Our results showed an increased risk of death for patients with T2DM similarly than previous studies conducted in high‐income countries . However, the strength of the association seems to be stronger in LA compared with other regions.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results showed an increased risk of death for patients with T2DM similarly than previous studies conducted in high‐income countries . However, the strength of the association seems to be stronger in LA compared with other regions.…”
Section: Discussionsupporting
confidence: 73%
“…As the diabetes is less controlled in LA, it can be assumed that mortality because of T2DM may be higher . Metabolic control in general is also important because uncontrolled lipid profiles may increase mortality among people with T2DM . Ethnicity, genetics as well as cultural and health backgrounds may account for differences in T2DM mortality .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a cause of low HDL and low HDL is a risk factor for cardiovascular disease in the diabetic patient. 39 Furthermore, cardiovascular disease is reported to be the most prevalent cause of death in diabetic patients. 40,41 Co-morbid conditions that predicted mortality in this study were anemia, hypotension, cardiac failure, and renal impairment.…”
Section: In 2009mentioning
confidence: 99%
“…(1) on our recent article on HDL cholesterol (HDL-c) as a residual risk factor for vascular events and all-cause mortality in patients with type 2 diabetes (T2D) (2). The findings of our study in the Second Manifestations of ARTerial disease (SMART) cohort showed that higher HDL-c is related to an unexpected higher risk of cardiovascular events (hazard ratio [HR] 1.10, 95% CI 1.07-1.21) and all-cause mortality (HR 1.14, 95% CI 1.07-1.21) in patients with very low levels of LDL cholesterol (LDL-c) (,2.0 mmol/L).…”
mentioning
confidence: 99%
“…The SMART cohort (7) is a unique cohort consisting of 1,829 high-risk T2D patients of whom 61% receive lipid-lowering treatment (29% usual dose; 32% intensive lipid-lowering therapy) (2). These patients have a median duration of diabetes of 4 years (interquartile range [IQR] 1-9) and the majority (66%) has clinical manifest vascular disease (2). The cohort studied by Aryan et al (1) seems to consist of a healthier study population compared with the SMART cohort (e.g., age 55 6 10 years vs. 60 6 10 years; males 44% vs. 70%).…”
mentioning
confidence: 99%